Contesting global governance : multilateral economic institutions ad global social movements - Robert, O'Brien (Cambridge, U.K. : , 2000 : Cambridge University Press, 2000)
Includes bibliographical references and index
Keywords: International Monetary Fund; International trade agencies; International trade -- Social aspects; World Bank; World Trade Organization